ANALISIS UKURAN PERUSAHAAN, FCF DAN KEBIJAKAN HUTANG TERHADAP KINERJA KEUANGAN PERUSAHAAN FOOD AND BEVERAGE - Gusmao, Eunike Frentelina (Universitas Indo Global Mandiri Palembang, 2022)
The purpose to be achieved in this study is to empirically examine the influence of variables in Company Size, Free Cash Flow, and Debt Policy on Financial Performance on Food and Beverage companies listed on the Indonesia Stock Exchange. The period used in this study is 4 (four) years, which is from 2017 to 2020. The population used in this study were 30 food and beverage companies that have been and are still listed on the Indonesia Stock Exchange in 2017-2020. The sampling technique was purposive sampling so that it is obtained by as many as 20 companies. The data analysis technique was multiple linear regression. The results of this study showed that the size of the company had a significant effect on the company's financial performance, Free Cash Flow also had a significant effect on financial performance,Â while for debt policy represented by DER has an insignificant effect on financial performance.